2013
DOI: 10.1890/11-1982.1
|View full text |Cite
|
Sign up to set email alerts
|

An innovative aerial assessment of Greater Yellowstone Ecosystem mountain pine beetle‐caused whitebark pine mortality

Abstract: Abstract. An innovative aerial survey method called the Landscape Assessment System (LAS) was used to assess mountain pine beetle (MPB; Dendroctonus ponderosae)-caused mortality of whitebark pine (Pinus albicaulis) across the species distribution in the Greater Yellowstone Ecosystem (GYE; 894 774 ha). This large-scale implementation of the LAS method consisted of 8673 km of flight lines, along which 4653 geo-tagged, oblique aerial photos were captured at the catchment level (a subset of 12-digit USGS hydrologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
80
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(85 citation statements)
references
References 37 publications
(32 reference statements)
2
80
3
Order By: Relevance
“…Previous studies have observed >50% mortality of whitebark pine trees at smaller spatial scales [4,11,12], and our results extend this benchmark to the entire US range of whitebark pine. This level of mortality is dramatic and rare in other tree species with such broad geographic distribution and ecological importance, except among species susceptible to broad-scale fungal or insect infestations, such as chestnut blight, Dutch elm disease, and emerald ash borer, all of which have caused greater than 50% mortality in their host populations in eastern Canada [29].…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Previous studies have observed >50% mortality of whitebark pine trees at smaller spatial scales [4,11,12], and our results extend this benchmark to the entire US range of whitebark pine. This level of mortality is dramatic and rare in other tree species with such broad geographic distribution and ecological importance, except among species susceptible to broad-scale fungal or insect infestations, such as chestnut blight, Dutch elm disease, and emerald ash borer, all of which have caused greater than 50% mortality in their host populations in eastern Canada [29].…”
Section: Discussionsupporting
confidence: 85%
“…Whitebark pine is considered a foundational species given its importance for snowpack retention [5,9] and provision of food and habitat for wildlife such as grizzly bears (Ursus arctos horribilis), Clark's nutcrackers (Nucifraga columbiana), and American red squirrels (Tamiasciurus hudsonicus) [10]. Mortality rates exceeding 50% of trees have been observed in previous studies of whitebark pine at local to regional scales [4,11,12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the Canadian 57 Rockies, mean WPBR infection levels have risen from 42% in 2003-2004to 52% in 200958 (Smith et al 20082013), with mortality increasing from 18% to 28% over the same time period. 59…”
Section: Introduction 41mentioning
confidence: 99%
“…Biotic factors introduce another level of uncertainty into predictions, particularly when they generate an additional source of environmental stress, such as the widespread impact of mountain pine beetles on pine tree mortality in North America [21]. Perhaps the most important biotic factor is human population growth and the impacts of more than 7 billion people on a natural environment that is increasingly under stress [22].…”
mentioning
confidence: 99%